Mechanosensitive channels: stress relief. - Biggin, P; Sansom, MS (2003)
Bacterial responses to decreasing osmolality involve mechanosensitive channels. The crystal structure has been determined of the small conductance mechanosensitive channel (MscS) from Escherichia coli, providing new insights into mechanical and voltage sensing by this and other channel proteins.